Dalpiciclib Combined With Pyrotinib and Letrozole in Women With HER2-Positive, Hormone Receptor-Positive Metastatic Breast Cancer (LORDSHIPS): A Phase Ib Study - Zhang, Jian; Meng, Yanchun; Wang, Biyun; Wang, Leiping; Cao, Jun; Tao, Zhonghua; Li, Ting; Yao, Wenqing; Hu, Xichun (Frontiers in Oncology, 2022)
Purpose The LORDSHIPS study aimed to explore the safety and efficacy of a novel fully oral triplet combination of dalpiciclib (a potent cyclin-dependent kinase 4/6 inhibitor), pyrotinib (a HER2 tyrosine kinase inhibitor) and endocrine therapy letrozole in patients with HER2-positive, hormone receptor (HR)-positive metastatic breast cancer (MBC) in the front-line setting. Patients and Methods Postmenopausal women with HER2-positive, HR-positive MBC were recruited in the dose-finding phase Ib trial. A standard 3 + 3 design was used to determine safety, tolerability, and recommended phase II dose (RP2D) for the combination. Results A total of 15 patients were enrolled to three dose combination cohorts (letrozole/pyrotinib/dalpiciclib, level/I: 2.5/400/125 mg, n=5; level/L1: 2.5/400/100 mg, n=6; level/L2: 2.5/320/125 mg, n=4). Three patients experienced dose-limiting toxicities (level/I, n=2; level/L1, n=1) and level/L2 was identified as RP2D. The most frequent grade 3-4 adverse events were neutropenia (46.7%), leukopenia (40.0%), oral mucositis (26.7%) and diarrhea (20.0%). The confirmed objective response rate (ORR) was 66.7% (95% CI: 38.4% to 88.2%). The confirmed ORR of study treatment as first line (1L) and second line (2L) HER2-targeted therapy was 85.7% (6/7) and 50.0% (4/8), respectively. Median progression-free survival (PFS) was 11.3 months (95% CI: 5.3 months to not reached). PFS in 1L setting was not reached yet, while PFS in 2L setting was 10.9 months (95% CI: 1.8 to 13.7 months). Conclusions The fully oral combination of dalpiciclib, pyrotinib and letrozole is a promising chemotherapy-sparing treatment option for HER2-positive, HR-positive MBC patients. The planned dose-expansion phase II study is ongoing. Clinical Trial Registration ClinicalTrials.gov, identifier NCT03772353.